Faktor Risiko Komplikasi Preeklampsia Berat Pada Ibu Bersalin Di RSUD dr. Adjidarmo - Rina Kartikasari; Ayu Fitriani; Ayu Kurnia Anggraeni (Borneo Nursing Journal (BNJ), 2025)
Preeclampsia is a major cause of increased maternal and neonatal morbidity and mortality. The prevalence of preeclampsia cases in developing countries is seven times higher than in developed countries. which is around 1.8%-18%. Preeclampsia tends to increase and become a medical complication in pregnancy and childbirth. The purpose of this study was to determine the relationship between risk factors for complications of severe preeclampsia in terms of maternal age, parity, gestational age and comorbidities. The method used in this research is quantitative with a case control design. The study sample size was 366 respondents using the total sampling technique. The results showed that there was a relationship between gestational age and complications of severe preeclampsia (α <0.05). However, there was no relationship between maternal age, parity, and comorbidities with complications of severe preeclampsia (α > 0.05). It is recommended for every health service in Lebak Regency, especially RSUD dr. Adjidarmo to be able to hold annual evaluations with type 1 health service partners in treating emergency patients.